The Haemodynamic and Pathophysiological Mechanisms of Calcific Aortic Valve Disease - Lydia Hanna; Chlöe Armour; Xiao Yun Xu; Richard Gibbs (Biomedicines, 2022)
The aortic valve (AoV) is the outflow valve for the left heart [...]